(untitled) (Anclajes, 2024)
From the perspectives of everyday aesthetics and hermeneutics, this paper analyzes Pequod (1995), a Vitor Ramil novel set in the Brazilian pampa and conceived around the unique features offered by the experience of cold weather. By analyzing the thoughts and actions of Pequod’s characters, our main goal is to point out how a vital relationship with weather leads to an existential stance, or philosophy of life, aimed at understanding the world.